A retrospective study of demographic proﬁle and outcome of Sever acute respiratory illness (SARI) in Iraq - Dawood, Haider; Mahdi, Sinan Ghazi (Journal of the Faculty of Medicine Baghdad, 2021)
Abstract Background Severe acute lower respiratory infection (SARI) is one of the major causes of morbidity and mortality, especially in developing countries. There is a large global variation in the epidemiology, clinical management and outcomes, including the mortality Aim of the study: To describe the demographic features, Province of residence, occupation and outcomes of patients SARI. Patients and Methods: A retrospective study of 1009 patients involved in the study, between the first of January 2019 and twenty eight of December 2019. From the medical records in Communicable Diseases Control Centre (CDC) office in Baghdad. Results: 1009 patients, 406 with positive for influenza A, and 603 with negative for influenza, the highest incidence was in the age group between 0-10 years for both positive (19.7%) and negative (25.0%) influenza A. Male higher (56.7%) than female in influenza A group, but female is higher (50.4%) in those with negative influenza group. The incidence in Baghdad is higher than other governments for both groups. Freelance is higher than other occupations (31.8%) for positive and housewife (32.2%) for negative influenza A. Death was 6.4% for positive and 1.5% for negative influenza A, the higher mortality rate was in male in age group 0-10 year for both positive (30.8%) and negative (18.9%)influenza A. Conclusion: influenza A is an important cause of SARI, childhood is a high risk for SARI who have high mortality rate especially in male. Freelance and housewife have high occupation risk for SARI. Baghdad has the higher rate than other governments for SARI In Iraq.